Why do bank runs look like panic? A new explanation - Yehning Chen; Iftekhar Hasan (Bank of Finland, 2006)
This paper demonstrates that, even if depositors are fully rational and always choose the Pareto dominant equilibrium when there are multiple equilibria, a bank run may still occur when depositors' expectations of the bank's fundamentals do not change.More specifically, a bank run may occur when depositors learn that noisy bank-specific information is revealed, or when they learn that precise bank-specific information is not revealed.The results in this paper are consistent with empirical evidence about bank runs. It also implies that suspension of convertibility can improve the efficiency of bank runs.
URN:NBN:fi:bof-20140807678
Keywords: G21; G28; 330; bank run; banking panic; suspension of convertibility